2015
DOI: 10.1158/0008-5472.can-14-1752
|View full text |Cite
|
Sign up to set email alerts
|

CEACAM1-3S Drives Melanoma Cells into NK Cell-Mediated Cytolysis and Enhances Patient Survival

Abstract: CEACAM1 is a widely expressed multifunctional cell-cell adhesion protein reported to serve as a poor prognosis marker in melanoma patients. In this study, we examine the functional and clinical contributions of the four splice isoforms of CEA-CAM1. Specifically, we present in vitro and in vivo evidence that they affect melanoma progression and immune surveillance in a negative or positive manner that is isoform specific in action. In contrast with isoforms CEACAM1-4S and CEACAM1-4L, expression of isoforms CEAC… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 47 publications
4
37
0
Order By: Relevance
“…The progression of melanoma is a complex multistep process orchestrated by a variety of cellular factors (Bastian, ). Although loss or reduced levels of the multifunctional carcinoembryonic antigen‐related cell adhesion molecule 1 (CEACAM1) expression have been detected in several tumor types, including colon (Neumaier et al., ), prostate (Luo et al., ), and breast cancer (Riethdorf et al., ), neo‐expression of CEACAM1 acts as a driver of melanoma cell invasion, thereby favoring metastatic spread (Ebrahimnejad et al., ; Markel et al., ; Ortenberg et al., ; Thies et al., ; Ullrich et al., ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The progression of melanoma is a complex multistep process orchestrated by a variety of cellular factors (Bastian, ). Although loss or reduced levels of the multifunctional carcinoembryonic antigen‐related cell adhesion molecule 1 (CEACAM1) expression have been detected in several tumor types, including colon (Neumaier et al., ), prostate (Luo et al., ), and breast cancer (Riethdorf et al., ), neo‐expression of CEACAM1 acts as a driver of melanoma cell invasion, thereby favoring metastatic spread (Ebrahimnejad et al., ; Markel et al., ; Ortenberg et al., ; Thies et al., ; Ullrich et al., ).…”
mentioning
confidence: 99%
“…Around 80% of all malignant melanoma lesions express CEACAM1 (Ortenberg et al., ; Ullrich et al., ), and moreover, its expression impacts on melanoma cell immunogenicity (Chen et al., ; Ullrich et al., ). Understanding the role of CEACAM1 and what drives its tightly controlled expression in melanoma is a key issue that may offer insights into the process of melanoma progression.…”
mentioning
confidence: 99%
“…The expression of CEAC AM1 varies between tumors. It is down-regulated in colon carcinomas, hepatocellular carcinomas, renal cancer, and breast cancer, while up-regulated in metastatic and malignant melanomas and lung cancer [2,3]. CEACAM1 acts as a pathogen receptor and plays the important role in cell proliferation, angiogenesis, apoptosis, and tumor metastasis [4].…”
Section: Introductionmentioning
confidence: 99%
“…showing that MITF stimulates the expression of the gene encoding the cell adhesion molecule CEACAM1 (Ullrich et al., ). Based on previous studies, overexpression of CEACAM1 in melanoma cells increases cell invasion and migration (Ebrahimnejad et al., ; Ullrich et al., ) likely through mechanisms involving interaction with β‐integrin and filamin (Brummer et al., ; Klaile et al., ) as well as N‐cadherin (Liu et al., ). On the other hand, we recently observed that another cellular adhesion molecule, MCAM, also known as CD146, is repressed by MITF in mouse melanoblasts (melb‐a cells), a repression that leads to inhibition of melanoblast migration (Rao et al., ).…”
mentioning
confidence: 95%
“…As usual, however, details are important. The evidence that CEACAM1 promotes migration is based on overexpression (Ullrich et al., ), that is, under conditions where MITF levels are low and hence different from the more physiological conditions where MITF and CEACAM1 levels go hand in hand. In fact, to our knowledge, the role of CEACAM1 in invasion has not yet been confirmed by experimental downregulation in an invasive melanoma.…”
mentioning
confidence: 99%